A comparison of hysterosalpingography and laparoscopy in the evaluation of tubal factors in female infertility - Gupta, Ankita; Upreti, Purnima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: WHO defines infertility as “failure to conceive after having regular, unprotected intercourse for one year. Factors responsible - male factors (20-30%), female factors (40-55%), combined male and female factors (10-40%) and unexplained infertility (10-20%). Amongst female factors, tubal factors are responsible for 25-30% of infertility. Hysterosalpingography and diagnostic laparoscopy with chromopertubation are widely used in the evaluation of tubal factors of infertility. The aim of this study was to compare findings of HSG and diagnostic laparoscopy with chromopertubation for tubal patency in infertile women. Methods: An observational study, done on a total of 125 females suffering from primary and secondary infertility who underwent HSG and then 97 patients who gave consent, underwent diagnostic laparoscopy with chromopertubation. The data was entered in MS excel spreadsheet and analysis was done using statistical package for social sciences (SPSS) version 21.0. Results: Primary infertility cases were more than secondary infertility cases. Mean age of patients was found to be 28.92±5.33 years. Most common tubal abnormality found on hysterosalpingography and chromopertubation was bilateral tubal block. Inter rater kappa agreement used and significant agreement found between hysterosalpingography and chromopertubation with kappa value of 0.612. Conclusions: From this study authors conclude that HSG and laparoscopy with chromopertubation are complimentary to each other. Laparoscopy helps in identification of tubal and non-tubal factors like intra-abdominal and pelvic adhesions, endometriosis etc. and simultaneously they can be treated while HSG helps in evaluation of tubal factors as well as of intra-uterine factors like synechiae, polyps etc.